Copyrights in Costa Rica - López López, Flor (1998)
Copyright has been the subject of discussion in national and international fora,  where a large number of interests are involved, both personal and economic. Coast Rica has not been the exception. Its importance and the protection provided by the country's legal system is of such magnitude that many of the benefits we receive as a nation (exemptions, preferential tariffs, export quotas) have been subject to the protection granted by the Costa Rican State to this type of rights.